METHODS OF MOLECULAR DIAGNOSTICS FOR FISH SPECIES IDENTIFICATION - T. A. Fomina; V. Yu. Kornienko; M. Yu. Minaev (Пищевые системы)
The growth in demand for fish products as a result of globalization of trade caused a risks and threats of selling poor-quality and falsified fish products. This has become a great problem both for supervising agencies and for consumers.Many countries have regulations on food labelling and safety. For example, in the Russian Federation, Republic of Belarus and Republic of Kazakhstan has been passed the Technical Regulation of the Customs Union TR CU022/2011 “Food products in part of their labeling” that aims to prevent misinformation of consumers to ensuring realization of consumer rights to reliable information about food products, and Technical Regulation TR EAEU040/2016 “On safety of fish and fish products” requires indication of the zoological name of the species of the aquatic biological resource or the object of aquaculture.Fish species identification is traditionally carried out based on external morphological traits. However, it becomes impossible to identify species by ichthyological traits upon fish cutting, if the head and fins are removed, and the body is cut on pieces (especially, in case of fillets) and even more so upon technological processing. In this case, objective analytical methods of species identification are used, which are based on ELISA or PCR. However, DNA‑based methods have several advantages compared to ELISA methods and complement traditional morphological identification methods. This paper gives a wide overview of the most recent and used methods of fish species identification based on DNA analysis such as single-strand conformation polymorphism (SSCP) analysis, species-specific PCR, real-time PCR, polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP), DNA barcoding, Sanger sequencing and next-generation sequencing (NGS).